Penerapan Metode Demonstrasi Dalam Tata Cara Berwudhu Pada Anak Usia Dini Pada Program Rumah Pintar Di Desa Malahayu - Mubayinah; Mu'minah; Adawiyah, Robiah Adawiyah (EDUCATIVA, 2024)
This research examines the effectiveness of the demonstration method in  teaching ablution procedures to young children through the Smart House program in Malahayu Village. The demonstration method was chosen to provide clear visual examples to children, with the aim of improving their understanding and skills in performing ablution. This research shows that the use of the demonstration method can significantly improve children's ablution skills and make the learning process more interactive and interesting. This research uses the demonstration method in ablution learning sessions for early childhood. This program is carried out over four meetings in one week. Data was collected through direct observation and interviews with parents as well as observing the results of children's practice. The research results showed that children showed increased  understanding and skills in carrying out ablution after following the demonstration method. Observations also revealed that children more easily remember the steps for performing ablution and are more enthusiastic in practicing it. The demonstration method has proven to be effective in teaching the procedures for performing ablution to young children. The Smart Home Program in Malahayu Village has succeeded in improving children's skills and making learning more fun. It is recommended to continue using this method in future early childhood education programs.